Relationship between Altitude and Juniper Genus Tree-Rings Width Case Study: Juniperus Habitats in North of Kerman Province - Iain Robertson (Ecology of Iranian Forest, 2020)
In this research, the role of altitude at Juniperus trees growth rings width in North Mountains of Kerman province has been investigated. Juniperus is one of the main pillars of natural ecosystems in Iran's mountainous forests. High mountains with vast expanse in Kerman province has caused the formation of tree coverings such as Juniperus and has created suitable habitats for Dendrochronology studies. However, most of the Dendrochronology studies in Iran are related to Zagros, Alborz and Hyrcanian forest, and no research has been carried out in Kerman province. The habitat of this study is located in the northern mountainous area of Kerman province, almost among the three counties of Ravar, Zarand and Kuhbanan. In this research, 128 cores from 64 Juniperus trees has taken in 4 sites of habitat by using an Increment Borer. These 4 sites and the difference in altitude between the lowest and highest trees of them are Kooh-e-gav 349 meters, Bid-e-shikh 401 meters, Rood-e-kor 478 meters and Galouband 215 meters. After preparing the samples and enhancing their visual clarity, the number and width of the rings were counted and measured by LINTAB and TSAPWin software with a precision of 0.01 millimeters. The Cross-Dating between two cores of any tree was performed by TSAP and the results of GLK, CDI, GSL, CC, and T-v statistics showed the optimum quality of Cross-Dating for growth series that obtained from the trees. The relationship between altitude differences and average ringwidth was measured using Pearson and Spearman correlation coefficients for 3 sites and all trees. Results of Pearson coefficients (Kooh-e-gav: -0.67, Bid-e-shikh: -0.75, Rood-e-kor: -0.59 and all trees: -0.45) and Spearman (Kooh-e-gav: -0.70, Bid-e-shikh: -0.79, Rood-e-kor: -0.33 and all trees: -0.30) showed that between the altitude and average ringwidth variables in the first two sites, the negative correlation is high, and on the third site as well as the all trees, there is a moderate negative correlation.